INVESTIGATIONS OF THE FORCED TORSIONAL VIBRATIONS IN THE SAW UNIT OF A KIND OF WOOD SHAPERS, USED IN THE WOOD PRODUCTION (Innovation in Woodworking Industry and Engineering design, 2026)
The proposed study presents a numerical investigation of the forced torsional vibrations in the wood shaper’s saw unit caused by the variable moments on the drive electric motor and the wood shaper’s saw. The influence on the vibrations of the blades’ number of the saw, which really work, is investigated. This research is done on the base of a concrete mechanic-mathe-matical model for investigation of the torsional vibrations of a wood shaper’s saw developed by the authors. The main features in the construction of this kind of wood shapers are rendered an account in this model. The investigation`s results can be used as a base for making some concrete and well-founded recommendations concerning the operation of these machines. These recommendations are important for increase of reliability of the wood shapers as well as the accuracy and quality of their production.